Development of multiple-breath-helium-washout system for lung function studies - Wang, Jau-Yi (2009)
This thesis discusses the development of the multiple-breat h-helium washout (MBHW) measurement for lung-function study. Multiple-breath washout (MBW) has been regarded as a sensitive technique to study the ventilation inhomogeneity in conducting or acinar airways. The tracer gas washed out from the lungs breath by breath is monitored. By analysing the concentration of the tracer gas versus the expired tidal volumes, the washout results provide two indices Scond and Sacin which reflect the degree of ventilation inhomogeneity. Scond is the increasing rate of the noramlised phase III slopes breath by breath while the Sacin is the normalised phase III slope from the first breath with the subtraction of Scond. The higher Scond value the greater ventilation inhomogeneity in the conductive airways while the higher Sacin value the greater ventilation inhomogeneity in the acinar airways. Traditionally, nitrogen is used as the tracer gas, washed out by the pure oxygen in a multiple-breath-nitrogen washout (MBNW) measurement. It is usually chosen because it is the gas we normally breathe and has no direct influence on physiology unlike oxygen. In this study,4He gas is used as the tracer gas instead. Since helium is less dense and has higher diffusivity than nitrogen, it is believed that it will be able to reach deeper into our lungs in a given time. Therefore, helium washout may provide more ventilation information especially in the small airways. In our MBHW system, a quartz tuning fork with a resonant frequency 32768Hz is used as the gas density sensor. The resonant frequency of the tuning fork is linearly related to the surrounding gas density. The helium concentr ation is given by eliminating all other gas components and calculating it from the tuning fork signal. Considering other components of our expiration, the carbon dioxide is detected by the infrared sensor, and the water is filtered out by a trap. We have performed the washout measurements on 11 volunteers, three of them have been diagnosed having mild lung diseases (asthma), two are smokers, and the other five are normal healthy people. The peak expiratory flow is also measured for each subject. The single breath MBHW curves from asthmatic people have higher normalised phase III slopes and higher Scond or Sacin values. This shows a greater conductive or acinar ventilation inhomogeneity in asthmatics’ lungs. The lung clearance washout curves are fitted with a summation of two exponential curves which represent two compartments with different ventilation rates. The compartment with higher decay rate represents the better-ventilated compartment and the other one is the poorly-ventilated compartment. Subjects with larger proportion of poorly-ventilated compartments have a lower peak expiratory flow rate compared to the predicted values. A 2.2-litre lung model has been built. A loud speaker has been used to simulate the movement of the diaphragm. MBHW measurements have been performed on the lung model which has a 0- to 4-generation dichromatic structure. The washout results from the lung models is compared to the results from the real lungs.